DEVELOPMENT OF TYPICAL TECHNICAL SOLUTIONS FOR RECONSTRUCTION FLAT COATINGS OF RESIDENTIAL BUILDINGS AND SERIES 1-464 1-480 - and and (Municipal economy of cities. Series: «Economy science», 2013)
We present the findings of our research related to the operating performance improvement of residential buildings that form part of the first large-scale series 1-464 and 1-480. The reconstruction of flat (combined with the roof) cover is demonstrated by 2 fundamental design solutions of hip roofs with arrangement of cold attic floor or garret. The model technical solutions were developed using 4-6-section buildings of the said series as an example by using wooden and metallic bearing structures subject to the heat insulation requirements.